Analisis Sifat Fisikokimia dari Beberapa Minyak Kemasan Hasil Penggorengan Tempe - Farhan, Muhammad; Azhar, Minda; Etika, Sri Benti; Pernadi, Niza Lian; Sabrina, Joya; Rahmi, Fathaniah Raviqa; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
Cooking oil is one of the staple ingredients for cooking which is very popular in Indonesian society. The cooking oil most often used for cooking by the community is palm oil, because it is easy to obtain and has a relatively affordable price. But on the other hand cooking oil which is repeatedly heated at high temperatures can have harmful effects on the body, especially with the presence of solutes in the ingredients that are fried. This study aims to determine the quality of palm oil from tempe frying which contains vegetable protein for 1 hour at 160 C. The cooking oil is heated for 1 hour then put in the tempe and removed after it is cooked, after 1 hour the oil is cooled and its quality is tested by testing the density, flow rate, acid number and saponification number. The results showed that after cooking for 1 hour testing the tempe frying oil, the quality of the oil based on the quality standard value was bimoli, followed by pure essence and fortune. The quality of bimoli oil from tempe frying for one hour was with a density of 0.9233 gr/mL, a flow rate of 3.805 mL/s, an acid number of 8.0536 mgKOH/g and a saponification number of 16.091 mgKOH/g.